Life cicle assessment of Italian ornmental stones. Analysis of processes and development of an adaptable model - Bianco, Isabella; Blengini, Gian Andrea (Italian journal of engineering geology and environment, 2017)
<span data-sheets-value="{"1":2,"2":"The Italian traditional field of dimension stone is currently experiencing a growing interest toward the application of the sustainability principles. In this framework, the main aim of this ongoing PhD project is to create a flexible tool able to support the environmental assessments of Italian stone companies. The methodology is aligned with the Life Cycle Approach and it analyses the cradle-to-gate production chain of both soft stones (marbles) and hard stones (granites). Because of the lack, in\rLCA databases, of quarry specific and process specific data, it has been necessary to collect information directly on the field. This allowed to investigate more accurately the resources, energy and emissions involved in the most widespread techniques of extraction and transformation. The inventory phase is then followed by the realization of an LCA model able to be adapted according to the specific firms productions. This aim is reached by choosing a flexible structure for the model and\rby setting customizable parameters. Final goal of this study is to allow stone companies to employ the model for improving their processes, for better marketing the products or for developing further researches."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">The Italian traditional field of dimension stone is currently experiencing a growing interest toward the application of the sustainability principles. In this framework, the main aim of this ongoing PhD project is to create a flexible tool able to support the environmental assessments of Italian stone companies. The methodology is aligned with the Life Cycle Approach and it analyses the cradle-to-gate production chain of both soft stones (marbles) and hard stones (granites). Because of the lack, in LCA databases, of quarry specific and process specific data, it has been necessary to collect information directly on the field. This allowed to investigate more accurately the resources, energy and emissions involved in the most widespread techniques of extraction and transformation. The inventory phase is then followed by the realization of an LCA model able to be adapted according to the specific firms productions. This aim is reached by choosing a flexible structure for the model and by setting customizable parameters. Final goal of this study is to allow stone companies to employ the model for improving their processes, for better marketing the products or for developing further researches.